2020
DOI: 10.1111/jocd.13616
|View full text |Cite
|
Sign up to set email alerts
|

A review of fatty acids influencing skin condition

Abstract: Background Fatty acids are common raw materials in cosmetics and also are an important component of skin surface lipids, and their composition and amount affect the skin condition. Aims The purpose of this article was to review the results of basic research on fatty acids as skin surface lipids. Methods An extensive literature search was conducted using PubMed, Web of Science, and other databases for articles on fatty acids from 1993 to 2020. Results This article provides an overview of the mechanisms of fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 35 publications
0
24
0
1
Order By: Relevance
“…Likewise, medium-chain fatty acids protect against inflammation and tumor factors. In addition, short-chain fatty acids can provide anti-inflammatory effects and initiate an immune response [15]. Cui et al [16] suggested the antibacterial and anti-inflammatory properties of fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, medium-chain fatty acids protect against inflammation and tumor factors. In addition, short-chain fatty acids can provide anti-inflammatory effects and initiate an immune response [15]. Cui et al [16] suggested the antibacterial and anti-inflammatory properties of fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…28 In our previous study, the decrease of saturated FA content was an important lipid marker for the weakening of skin barrier function, while the increase of unsaturated FA content was an important lipid marker for the destruction of skin barrier function. 29 In addition, although the contents of glycerolphospholipids (GPs) and ceramides (Cers) did not show a trend change, it is worth noting that both GPs and Cers have a positive effect on skin barrier function. 15,30 It seems reasonable, because compared with young men, the contents of GPs and Cers showed obvious effect-dose relationship when skin barrier function was weakened or destroyed.…”
Section: The a Sso Ciati On B E T Ween The Effec T Of S E X Hormone S On S Ebum And S K In Cond Iti Onmentioning
confidence: 98%
“…Many kinds of fatty acids can be used as raw materials, such as lauric acid, myristic acid, palmitic acid, and stearic acid. In addition, FAs are skin components as an important player in the maintenance of normal skin barrier function [99].…”
Section: Fatty Acylsmentioning
confidence: 99%